2021
DOI: 10.1108/jbim-12-2020-0540
|View full text |Cite
|
Sign up to set email alerts
|

Factors impacting digital transformations of the food industry by adoption of blockchain technology

Abstract: Purpose This study aims to blockchain facilitate information sharing among different players in the food industry, such as farmers, food suppliers and investors, enabling an effective decision-making process where the information about goods is traceable without any inherent risk. Although blockchain technology is emerging, its use in the food industry needs to be explored from different angles, such as organizations’ policy, adoption strategies and potential technology innovations which could positively impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 80 publications
2
28
1
Order By: Relevance
“…[4,49] BC technology is new, while BC-based traceability is immature and has potential for future research. [9,70] It promotes fair trade and enables one to make safe food purchase decisions. [46,57,61] BCT can be integrated into existing digital traceability systems.…”
Section: Description Of Benefits Referencementioning
confidence: 99%
See 1 more Smart Citation
“…[4,49] BC technology is new, while BC-based traceability is immature and has potential for future research. [9,70] It promotes fair trade and enables one to make safe food purchase decisions. [46,57,61] BCT can be integrated into existing digital traceability systems.…”
Section: Description Of Benefits Referencementioning
confidence: 99%
“…[61] BCT can be used as a digital service platform that the supply chain actors can access and use to provide or obtain data regarding their products, and AFSC managers can audit the product flow easily. [11,70] There is potential for the design and implementation of BCT-based TSs at lower and affordable costs, e.g., management overhead costs can be shared among blockchain network parties. [18] The benefits of BCT-based traceability systems in complex AFSC are expected to be maximized with future research on blockchain systems, as well as the development and implementation of innovative designs of such systems [66].…”
Section: Description Of Benefits Referencementioning
confidence: 99%
“…I4T can make firms more flexible and sustainable by improving product customization, automation processes, energy efficiency, product quality, productivity, sustainability, safety, decision-making processes, demand-supply of skills, etc. Acquiring an internal process using I4T such as blockchain can lead to the improved relational social capital of a firm by building trust between buyers and suppliers (Dehghani et al , 2021) and improving supply chain relationship (Kumar, 2020). The problem of green supplier selection and sourcing can also be addressed by proper execution of I4T (Fallahpour et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dehghani et al. (2021) highlighted that the blockchain enables information sharing among various players in the food industry, such as farmers, food suppliers and investors, enabling a role-based process in which information about goods is easily detectable and free of inherent risk.…”
Section: Introductionmentioning
confidence: 99%
“…Moretto and Macchion (2022) investigated the drivers and barriers of blockchain adoption in fashion SCs and highlighted the necessity of blockchain in tracking and tracing in fashion SC. Dehghani et al (2021) highlighted that the blockchain enables information sharing among various players in the food industry, such as farmers, food suppliers and investors, enabling a role-based process in which information about goods is easily detectable and free of inherent risk. The findings also found that perceived efficiency, accountability, standardisation, systems and technologies and track-and-trace factors positively influenced intent to use.…”
Section: Introductionmentioning
confidence: 99%